Carvacrol as potential quorum sensing inhibitor of Pseudomonas aeruginosa and biofilm production on stainless steel surfaces. (May 2017) - Tapia-Rodriguez, Melvin R.; Hernandez-Mendoza, Adrian; Gonzalez-Aguilar, Gustavo A.; Martinez-Tellez, Miguel Angel; Martins, Claudia Miranda; Ayala-Zavala, J. Fernando
Abstract: Pseudomonas aeruginosa biofilm confers resistance to antibiotics and biocides; therefore, it represents a problem to clinical and industrial settings. This bacterial organization is controlled by quorum sensing (QS), which depends of autoinducer molecules, e.g. acyl-homoserine-lactones that regulate production on virulence factors as pyocyanin. As a solution to this problem, carvacrol, present in most of the antibacterial essential oils could be a potential agent to inhibit QS for its ability to interact with cell membrane and protein receptors involved in biofilm formation. Therefore, this work evaluated the effect of carvacrol on pyocyanin production and biofilm formation of P. aeruginosa. Minimal inhibitory concentration (MIC) of carvacrol against planktonic P. aeruginosa was 7.9 mM; in addition, carvacrol was tested against Chromobacterium violaceum as model for anti-QS agents, showing a MIC of 0.7 mM. Lower concentrations of carvacrol to observed MICs were applied to observe changes in QS activity and biofilm production to avoid effect of cell death on mentioned parameters. Carvacrol inhibited P. aeruginosa biofilms (1.5–3 Log CFU/cm 2 ) at 0.9–7.9 mM, compared to non-treated bacteria on stainless steel surface. Pyocyanin production by P. aeruginosa was reduced up to 60% at 3.9 mM of carvacrol. Higher doses of carvacrol affected P. aeruginosa viability. Similar results were obtained for violacein production that is related to QS of C. violaceum, where carvacrol reduced up to 50% at 0.7 mM without affecting cell viability. These results showed that the inhibition of QS could be related with reduction of bacterial virulence and biofilm formation on stainless steel surfaces exposed to carvacrol. Highlights: Carvacrol inhibited biofilm formation of Pseudomonas aeruginosa. Anti-biofilm potential of carvacrol can be related to quorum-sensing interruption. Carvacrol could be exploited as anti-biofilm reagents in food interest surfaces.